Planning and spatial composition of Liepaja squares up to World War I - Ozola, Silvija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Planning of Liepaja on the Baltic Sea was determined by water course and islands of the River Liva, Livonia’s land commercial and military road from Königsberg (Kaliningrad) to Riga, which led along the seashore, apart from the Curonian fishermen settlements, but through Liva or Sand village on the sandbar. The flow of the River Liva originally coincided with the flow of the River Perkone. Around the 13th century the Liva port was created for shipping, trade and transhipment of goods. After devastation of the Sand village in 1418, the mouth of the River Liva was used for shipping; in the neighborhood, around the church, houses were built. Dwelling houses gradually occupied the territory to the River Perkone. Since the 16th mid- century from the southern part, alongside with the flow of the River Liva the Great Courland-Prussia dirt road led to the crossing through Liepaja, in the widening of it Hay Market (Heumarkt) was formed. The traffic flow divided in two directions – to the Old Market (Alter Markt), in the confluence of eight streets and to the trade centre in the western end of Ungera (Avotu) Street between Peldu and Skarnu (Ludviķa) Streets. The Liva River got choked up with sand and in 1538 it did not fit for shipping. In Ducatus Curlandiae et Semigalliae the official religion was declared Lutheranism. Next to the Old Market Square St. Anna’s wooden church (around 1587) was built. Craftsmen and merchants began to build their homes in the neighborhood. The public and social center of Libava (Libau) village formed. Lifestyle and occupation of population contributed to formation of the commercial center in the port area. In the neighborhood of Diku Street, where the customs garden, the Duke’s and private warehouses were situated, craftsmen and merchants' houses with black tarred walls had been built. From 1697 to 1703 a trading port canal was built. The urban area in 1705 expanded from the southern part of Siena tirgus to the bridge over the canal at the end of Lielā Street. Swedish army left Liepaja in September of 1709. Situation at the port in 1711 was evaluated as safe and the passenger traffic increased. Near the canal crossing place, a watch house was built. In 1737 piers had been completed to built of two rows of piles in the sea. Liepaja port could accommodate large vessels and enlarge trade relations with foreign countries. A shipping and transport center formed near the port. Business activities in the 18th century influenced urban planning – locations of building and streets. Crossings and broadenings of streets formed squares. Squres are important for spatial design and organization of traffic flow in city. Planning of Liepaja as an economically active city is determined by the main road directions to the major functional areas – administrative centers and squares – where a variety of activities took place: retail, manufacturing, transport services, transshipment of goods and cultural events. Squares of appropriate size and design were created for different purposes. They affected the spatial composition of the city by acquiring architectural dominance, functionally suitable configuration, building, and visual appearance. The aim of the study is to analyze the development of Liepaja planning and its changes up to World War I, and to determine the mutual correlations between different functional area planning solutions.